Long term measures of vestibulo-ocular reflex function in high level male gymnasts and its possible role during context specific rotational tasks - von Laßberg, C.; Campos, J. L.; Beykirch, K. A. (PLOS ONE, 2021)
In a prior publication, we described a previously unknown eye movement phenomenon during the execution of actively performed multiaxial rotations in high level gymnasts. This phenomenon was consistently observed during the phase of fast free flight rotations and was marked by a prolonged and complete suppression of nystagmus and gaze stabilizing "environment referenced eye movements" (EREM; such as the vestibulo-ocular reflex, optokinetic reflex, smooth pursuit and others). Instead, these eye movements were coupled with intersegmental body movements. We have therefore called it "spinal motor-coupled eye movements" (SCEM) and have interpreted the phenomenon to likely be caused by anti-compensatory functions of more proprioceptive mediated reflexes and perhaps other mechanisms (e.g., top-down regulation as part of a motor plan) to effectively cope with a new-orientation in space, undisturbed by EREM functions. In the phase before landing, the phenomenon was replaced again by the known gaze-stabilizing EREM functions. The present study specifically evaluated long-term measures of vestibulo-ocular reflex functions (VOR) in high level gymnasts and controls during both passively driven monoaxial rotations and context-specific multiaxial somersault simulations in a vestibular lab. This approach provided further insights into the possible roles of adaptive or mental influences concerning the VOR function and how they are associated with the described phenomenon of SCEM. Results showed high inter-individual variability of VOR function in both gymnasts and controls, but no systematic adaptation of the VOR in gymnasts, neither compared to controls nor over a period of three years. This might generally support the hypothesis that the phenomenon of SCEM might indeed be driven more by proprioceptively mediated and situationally dominant eye movement functions than by adaptative processes of the VOR.